Gender norms and intra-household allocation of labor: a CGE application to household economics - Arora, Diksha (International Center for Tropical Agriculture, 2017)
Presented by Diksha Arora (CIAT), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.